Pendekatan Pendidikan Agama Kristen Anak: Parenting Anak dalam Keluarga Kristen di Era Teknologi Digital - Halawa, Dian Trikusmawati; Stevanus, Kalis; Yulianto, Tomi (HARVESTER: Jurnal Teologi dan Kepemimpinan Kristen, 2024)
The development of digital technology has changed the landscape of human life, including in the context of the Christian family. In the era of rapidly developing digital technology, the challenges for Christian families in educating their children are increasingly complex. Through a literature approach, this research investigates the impact of digital technology on the formation of children's character and interpersonal relationships within the family. Through this research, it is hoped that Christian families will have understanding and knowledge in responding to parenting children in the digital era with the demands of changing digital technology. It can be concluded how important it is to approach children's Christian religious education in the family from an early age where parents act as figures/role models for children, dare to discipline children, parents build open communication and are full of warmth and parents provide intensive assistance to ensure that children stay connected to the spiritual and moral values taught in the Bible. AbstrakPerkembangan teknologi digital telah mengubah lanskap kehidupan manusia, termasuk dalam konteks keluarga Kristen. Pada era teknologi digital berkembang sangat pesat, tantangan bagi keluarga Kristen dalam mendidik anak-anak mereka semakin kompleks. Melalui pendekatan kepustakaan, penelitian ini menyelidiki dampak teknologi digital terhadap pembentukan karakter anak, dan hubungan interpersonal dalam keluarga. Melalui penelitian ini diharapkan keluarga Kristen mempunyai pemahaman dan pengetahuan dalam menyikapi parenting anak di era digital dengan tuntutan perubahan teknologi digital. Dapat disimpulkan betapa pentingnya pendekatan Pendidikan Agama Kristen Anak di dalam keluarga sejak dini, dimana orang tua berperan sebagai figur atau teladan bagi anak, berani mendisiplin anak, serta membangun komunikasi terbuka dan penuh kehangatan dan intensif, dan orang tua melakukan pendampingan untuk memastikan bahwa anak-anak tetap terhubung dengan nilai-nilai spiritual dan moral yang diajarkan dalam Alkitab.